What are the important technologies for bin picking? Technology analysis of robots in competitions based on a set of performance metrics. (17th April 2020) - Fujita, M.; Domae, Y.; Noda, A.; Garcia Ricardez, G. A.; Nagatani, T.; Zeng, A.; Song, S.; Rodriguez, A.; Causo, A.; Chen, I. M.; Ogasawara, T.
ABSTRACT: Bin picking is still a challenge in robotics, as patent in recent robot competitions. These competitions are an excellent platform for technology comparisons since some participants may use state-of-the-art technologies, while others may use conventional ones. Nevertheless, even though points are awarded or subtracted based on the performance in the frame of the competition rules, the final score does not directly reflect the suitability of the technology. Therefore, it is difficult to understand which technologies and their combination are optimal for various real-world problems. In this paper, we propose a set of performance metrics selected in terms of actual field use as a solution to clarify the important technologies in bin picking. Moreover, we use the selected metrics to compare our four original robot systems, which achieved the best performance in the Stow task of the Amazon Robotics Challenge 2017. Based on this comparison, we discuss which technologies are ideal for practical use in bin picking robots in the fields of factory and warehouse automation. GRAPHICAL ABSTRACT: